Employment protection legislation and wages - Marco Leonardi; Giovanni Pica (European Central Bank (ECB), 2007)
In a perfect labor market severance payments can have no real effects as they can be undone by a properly designed labor contract (Lazear 1990). We give empirical content to this proposition by estimating the effects of EPL on entry wages and on the tenure-wage profile in a quasi-experimental setting. We consider a reform that introduced unjust-dismissal costs in Italy for firms below 15 employees, leaving firing costs unchanged for bigger firms. Estimates which account for the endogeneity of the treatment status due to workers and firms sorting around the 15 employees threshold show no effect of the reform on entry wages and a decrease of the returns to tenure by around 20% in the first year and by 8% over the first two years. We interpret these findings as broadly consistent with Lazear's (1990) prediction that firms make workers prepay the severance cost.
Keywords: E24; J63; J65; 330; Costs of Unjust Dismissals; Regression Discontinuity Design; Severance Payments; Arbeitnehmerschutz; Beschäftigungssystem; Arbeitsmobilität; Lohn; Abfindung; Theorie